2018
DOI: 10.3389/fphar.2018.00082
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Long Non-coding RNA MIAT Sensitizes Lung Cancer Cells to Gefitinib by Epigenetically Regulating miR-34a

Abstract: Long non-coding RNA (lncRNA) myocardial infarction associated transcript (MIAT) was recently identified as oncogene in several cancers. However, the role of MIAT on acquired resistance in lung cancer and the underlying mechanisms remain unclear. Here, we showed that the expression of MIAT in lung cancer tissues was upregulated compared with adjacent tissues. LncRNA MIAT expression was associated with tumor size, lymph node metastasis, distant metastasis and TNM stage. Univariate analysis and multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 44 publications
1
40
0
1
Order By: Relevance
“…However, with respect to TSCC, no study has yet investigated the relationships between MIAT expression level and the prognosis of this disease. In our study, for the first time, we found that MIAT expression level TSCC specimen was significantly higher than that in adjacent nonneoplastic tongue tissue, this result was consistent with previous studies, 16,17 suggesting that MIAT was involved in the development of TSCC. In addition, correlation analysis showed that there is a significant positive correlation between MIAT levels in serum and MIAT was a risk factor for prognosis of TSCC within 12 months, whose high level means a poor prognosis of TSCC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, with respect to TSCC, no study has yet investigated the relationships between MIAT expression level and the prognosis of this disease. In our study, for the first time, we found that MIAT expression level TSCC specimen was significantly higher than that in adjacent nonneoplastic tongue tissue, this result was consistent with previous studies, 16,17 suggesting that MIAT was involved in the development of TSCC. In addition, correlation analysis showed that there is a significant positive correlation between MIAT levels in serum and MIAT was a risk factor for prognosis of TSCC within 12 months, whose high level means a poor prognosis of TSCC.…”
Section: Discussionsupporting
confidence: 93%
“…Li et al found that MIAT could interact with miR‐133, then promote the growth and invasion of pancreatic carcinoma cells, and indicate a poor prognosis. Study by Fu et al revealed that MIAT expression was associated with tumor size, lymph node metastasis, distant metastasis and TNM stage and was an independent factor for predicting the prognosis of lung cancer patients. However, with respect to TSCC, no study has yet investigated the relationships between MIAT expression level and the prognosis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Purified RNA was reverse transcribed into cDNA by using random primer with the QuantiTect Reverse Transcription Kit (Qiagen), and the presence of PAR5 transcripts was detected by qRT-PCR. Enrichment of PAR5 transcripts in the EZH2 immunoprecipitated lysate was calculated relative to the levels of PAR5 transcript in the rabbit IgG control sample, set equal to 1 [51,52].…”
Section: Rna Immunoprecipitation (Rip) Assaymentioning
confidence: 99%
“…Li et al found that MIAT contributed to the cell proliferation and metastasis of pancreatic carcinoma via interaction with miR‐133 . Fu et al demonstrated that MIAT was up‐regulated in lung cancer tissues and could sensitize lung cancer cells to gefitinib through epigenetically regulating miR‐34a . However, the function of MIAT in OS and the potential molecular mechanism are unknown.…”
Section: Introductionmentioning
confidence: 99%